1998
DOI: 10.1093/bja/81.4.529
|View full text |Cite
|
Sign up to set email alerts
|

Laser stimulation of acupuncture point P6 reduces postoperative vomiting in children undergoing strabismus surgery

Abstract: We conducted a double-blind, randomized, placebo-controlled study to investigate the effectiveness of P6 acupuncture on postoperative vomiting in children undergoing strabismus surgery. Acupuncture was performed by laser stimulation with a low-level laser. Laser stimulation of P6 was administered 15 min before induction of anaesthesia and 15 min after arriving in the recovery room. In the laser stimulation group, the incidence of vomiting was significantly lower (25%) than that in the placebo group (85%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(57 citation statements)
references
References 39 publications
2
52
0
3
Order By: Relevance
“…38 More recently, however, the effectiveness of acupuncture for the prophylaxis of PONV in children has been demonstrated (IIIA). [108][109][110][111] In a recent randomized placebo controlled study in patients undergoing breast surgery, Gan and colleagues reported similar efficacy of electroacupuncture at the P6 point and prophylactic ondansetron. Of interest electroacupuncture patients reported less pain compared with the other groups (IIIA).…”
Section: Non-pharmacological Techniquesmentioning
confidence: 95%
“…38 More recently, however, the effectiveness of acupuncture for the prophylaxis of PONV in children has been demonstrated (IIIA). [108][109][110][111] In a recent randomized placebo controlled study in patients undergoing breast surgery, Gan and colleagues reported similar efficacy of electroacupuncture at the P6 point and prophylactic ondansetron. Of interest electroacupuncture patients reported less pain compared with the other groups (IIIA).…”
Section: Non-pharmacological Techniquesmentioning
confidence: 95%
“…Most trials recruited healthy adults undergoing elective surgery. Seven trials recruited children (Butkovic 2005;Lewis 1991;Rusy 2002;Schlager 1998;Shenkman 1999;Wang 2002;Yentis 1992). One trial recruited both children and adults (Amir 2007).…”
Section: Description Of Studiesmentioning
confidence: 99%
“…There were 10 types of P6 acupoint stimulation: needle acupuncture (Dundee 1986;Dundee 1989;Sharma 2007;Streitberger 2004;Yentis 1992); infiltration of dextrose (Tavlan 1996;Wang 2002;Yang 1993); semipermanent needles (Andrzejowski 1996); electrical stimulation of needles (Amir 2007;Dundee 1989;Ho 1989;Rusy 2002); transcutaneous electrical nerve stimulation (Fassoulaki 1993;Gan 2004;Habib 2006;Ho 1989); laser stimulation (Butkovic 2005;Schlager 1998); an acu-stimulation device (White 2002;Zarate 2001); and acupressure (Agarwal 2000;Agarwal 2002;Alkaissi 1999;Alkaissi 2002;Allen 1994;Barsoum 1990;Duggal 1998;Ferrara-Love 1996;Gieron 1993;Harmon 1999;Harmon 2000;Ho 1996;Klein 2004;Lewis 1991;Samad 2003;Schultz 2003;Turgut 2007). Two studies used conventional peripheral nerve stimulation (Arnberger 2007;Liu 2008).…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Schlager et al (28) reported that the laser acupuncture technique was effective in paediatric ocular surgery cases (strabismus) as witnessed by a decrease in the PONV rate from 85% to 25%. Rusy et al (29) also concluded that the PONV rate decreased from 93% to 63% with the electro-acupuncture technique.…”
Section: Discussionmentioning
confidence: 99%